Mesoporous NiFe2O4 with Tunable Pore Morphology for Electrocatalytic Water Oxidation. Issue 1 (14th January 2021) - Simon, Christopher; Timm, Jana; Tetzlaff, David; Jungmann, Jonas; Apfel, Ulf‐Peter; Marschall, Roland
Abstract: Mesoporous NiFe2 O4 for electrocatalytic water splitting was prepared via soft‐templating using citric‐acid‐complexed metal nitrates as precursors. The mesopore evolution during thermal treatment was examined systematically giving insights into the formation process of mesoporous NiFe2 O4 . Detailed nitrogen physisorption analysis including desorption scanning experiments reveal the presence of highly accessible mesopores generating surface areas of up to 200 m 2 /g. The ability of the NiFe2 O4 powders to perform electrocatalytic oxygen evolution reaction under alkaline conditions was investigated, highlighting the advantages of mesopore insertion. The most active samples reach a current density of 10 mA cm −2 at an overpotential of 410 mV with a small Tafel slope of 50 mV dec −1, indicating an enhanced activity that originated from the increased catalyst surface. Abstract : Pores for gas evolution : Mesoporous nickel ferrite powders are synthesized with special attention to the mechanism of pore formation. The relation between porosity of the samples and performance in the electrocatalytic oxygen evolution reaction under alkaline conditions is investigated, including effects from electrochemically accessible surface and crystallite size.